HEAT TRANSFER AND PRESSURE DROP DURING CONDENSATION OF REFRIGERANT R-134A IN A HORIZONTAL TUBE BUNDLE - محمد عبد الله الصفاوي, عدنان; قصي شريف, زينب (Journal of Engineering and Sustainable Development, 2015)
The research is a theoretical study of heat transfer and pressure drop of two phase flow of refrigerants during condensation in horizontal tube banks and air flows across them in parallel direction under constant heat flux . (R134a) has been selected as a working fluid which is environment-friendly and is used as an alternative to (R12) in air conditioning and refrigeration systems and others industrial applications. The effects of different variables on the heat transfer operation and pressure drop were investigated, namely, air velocity ,air temperature, tube diameter, and the number of rows and columns of the tubes in addition to longitudinal and transversal pitch ratio . A computer program is built to calculate the heat transfer coefficient and pressure drop through condensation process using Finite Difference scheme. Engineering Equation Solver (EES) was employed as an assistant program to estimate physical and thermal properties of different refrigerant. Results showed a drop in pressure along the pipe , its value was decreased with increasing the tube diameter, air temperature and the transversal pitch in both in-line and staggered arrangements as well as the longitudinal pitch in staggered arrangement . Also the heat transfer coefficient between the fluid and the internal tube surface decreases along the tube length and increases with both of the number of tubes in rows and columns air velocity and longitudinal pitch in in-line arrangement. The results showed that the tube banks of staggered arrangement has a higher heat transfer coefficient than the in-line arrangement tube banks .